Protective effect of soy powder and microencapsulation on freeze-dried Lactobacillus brevis WK12 and Lactococcus lactis WK11 during storage - Gwak, Hyun Jung; Lee, Jong-Hee; Kim, Tae-Woon; Choi, Hak-Jong; Jang, Ja-Young; Lee, Sang Il; Park, Hae Woong (Food science and biotechnology, 2015)
Food-grade cryoprotective agents, i.e. , skim milk, soy powder, yeast extract, and trehalose were tested for viability of lactic acid bacteria (LAB, Lactobacillus brevis WK12 and Lactococcus lactis WK11) during freeze drying. Ten percentage of soy powder showed a strong protective effect upon viability of both LAB, showing 1.85×10 11 CFU/mL for L. brevis WK12 and 1.89×10 11 CFU/mL for L. lactis WK11. Microencapsulation in Ca-alginate beads increased viability of LAB, compared to nonencapsulated cells. Moreover, there was a synergetic effect on the stability of LAB when encapsulated LAB in Ca-alginate beads were soaked in 10% of soy powder prior to freeze-drying. When temperature increased, however, survival of LAB decreased. Four weeks after storage the highest viability was observed at -18°C for L. brevis WK12 and L. lactis WK11, showing 1.80×10 11 CFU/mL and 1.78×10 11 CFU/mL, respectively. These results suggest that soy powder may be useful for enhancing viability of LAB with microencapsulation.